Consideration of anisotropic material properties in mechanical design within early design phases - Gruber, Georg; Klein, Daniel; Ziegler, Philipp; Wartzack, Sandro (NordDesign 2012 - Proceedings of the 9th NordDesign Conference, 2012)
To achieve the goal of simulating the structural behavior of parts made of short fiber reinforced polymers with satisfactory accuracy and justifiable modeling effort, a new approach adapted to the needs of the early design steps was developed at the Chair of Engineering Design (KTmfk). Hereby, the various effects of material behavior are modeled by overlapping two different material models in one finite element definition. The anisotropic material properties are determined by an injection molding simulation. The complexity of the resulting fiber distribution is reduced to just three values per finite element. The paper's focus is the introduction of an automated method supporting the determination of the numerical material parameter and a new tensor based method enabling the averaging of the complex orientation state. The benefits of the new methods and a validation are presented.
CRIS-Team Scopus Importer:2020-04-28
Keywords: Early design steps; Fiber reinforced polymers; Lightweight design; Simulation